Royal Commission on the Ancient and Historical Monuments of Wales - Großbritannien - Commission on Ancient and Historical Monuments in Wales and Monmouthshire (2007)
[Dt.:] Die Royal Commission on the Ancient and Historical Monuments of Wales kümmert sich um das archäologische, architektonische und historische Erbe von Wales. Über Coflein, die Online-Datenbank, können Denkmäler und Gebäude über einen Index recherchiert werden (Thumbnails sind vergrößerbar). Daneben bietet die Website Informationen zur Vereinigung und ihren Aktivitäten und Publikationen. - [Engl.:] The Royal Commission on the Ancient and Historical Monuments of Wales is based in Aberystwyth. Maintains and curates the National Monuments Record of Wales (NMRW) holding the national collection of information about the archaeological, architectural and historical heritage of Wales and provides a public information service, drawing on both archival and published sources. Coflein the online database contains details of many thousands of archaeological sites, monuments, buildings and maritime sites in Wales, together with an index to the drawings, manuscripts and photographs. Sites can be displayed on Ordnance Survey maps and ordered geographically, as well as by text queries. The data can be searched by location, by type or by keyword.